(untitled) (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the relationship between workload and work stress of nurses in implementing nursing care in inpatient rooms. The method used is a cross-sectional survey with 69 respondents. The results showed that nurses had a light workload (68.1%) and nurses who experienced light work stress (60.9%). After statistical tests were carried out, it was found that there was a relationship between workload and work stress of nurses, with a value of p = 0.018 (<0.05). In conclusion, there is a relationship between nurses’ workload and work stress in the inpatient room of Luwuk Banggai Hospital. Keywords: Workload, Implementation of Nursing Care, Work Stress